2021
DOI: 10.4102/sajip.v47i0.1904
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership and follower trust in the leader: The effect of precariousness

Abstract: Orientation: In a business context characterised by precariousness and uncertainty, the importance of trusting leader-follower relationships is becoming critical to navigate imminent challenges preventing organisational sustainability and progress. The potential negative impact of related challenges could be reduced by encouraging leaders to adopt an authentic leadership style, culminating in various positive employee and organisational outcomes.Research purpose: This study investigated the impact of authentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…This study suggests that employees will have more trust in their employers if top executives demonstrate leadership authenticity (AL) attributes. The results of earlier studies by Kleynhans, Heyns, and Stander (2021), Farid, Iqbal, Khan, Ma, Khattak, and Naseer Ud Din (2020), Khalil and Siddiqui (2019), and Kim, David, Chen, and Liang ( 2022) are all in agreement with this finding. Third, the study proposed that among workers, OT highly predicted OC (H3).…”
Section: Discussion Of Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…This study suggests that employees will have more trust in their employers if top executives demonstrate leadership authenticity (AL) attributes. The results of earlier studies by Kleynhans, Heyns, and Stander (2021), Farid, Iqbal, Khan, Ma, Khattak, and Naseer Ud Din (2020), Khalil and Siddiqui (2019), and Kim, David, Chen, and Liang ( 2022) are all in agreement with this finding. Third, the study proposed that among workers, OT highly predicted OC (H3).…”
Section: Discussion Of Findingssupporting
confidence: 83%
“…Thus, the confidence of one's followers in their leader is impacted by the leader's own actions and demeanour. Kleynhans, Heyns, and Stander (2021) Farid et al (2020) showed that AL was positively associated with OT. In China, Qiu, Alizadeh, Dooley, and Zhang (2019) investigated how AL related to OT among 368 employees selected from the hospitality industry.…”
Section: Authentic Leadership and Organizational Trustmentioning
confidence: 97%
“…An example item is “There is a widely held belief that my organization is moving forward for the better” ( Ferres and Travaglione, 2003 ). A recent study that applied the WTS in a South African setting reported a composite reliability coefficient of.96 ( Kleynhans et al, 2021b ). Ramdas and Patrick (2019) administered the WTS successfully in their research.…”
Section: Methodsmentioning
confidence: 99%
“…It's been empirically measured by ability, compassion, honesty, and predictability (Kappmeier et al, 2021). Belief in the leader's actionsmore precisely, followers' expectation of a favourable result from the leader's choicesdepends on leadership trust (Kleynhans et al 2021;Vasudevan et al 2022). For leadership to be trusted, followers must have confidence in the leader's integrity and how they are treated (Engelbrecht et al, 2017).…”
Section: Descriptive Statisticsmentioning
confidence: 99%